ENDOCRINOLOGICAL RESPONSE OF RABBIT AFTER EXPOSURE OF OVARIES TO DIAGNOSTIC ULTRASOUND: Exposure of Ovaries to Diagnostic Ultra Sound - Butt, Shadab Ahmed; Tahir, Muhammad; Minhas, Liaqat Ali (Pakistan Armed Forces Medical Journal, 2018)
Objective: To study the serum progesterone and estradiol level in rabbit after exposed of their ovaries to ultrasound waves. Study Design: Experimental study. Place and Duration of Study: NIH, Islamabad, Army Medical College Rawalpindi from Mar 2006 to Sep 2006. Materials and Methods: Forty, adult, non pregnant female rabbits (Oryctolagus cuniculus strain) weighing 900 gm to 1500 gm were used. They were divided in four groups, each containing ten rabbits, Group I was taken as control. Ovaries of other three groups (group II, III and IV) were exposed to ultrasound (frequency of 3.5 MHz and intensity of 96 dB for two minutes) for 3, 6 and 12 days respectively. Two milliliter of blood samples was withdrawn after 24 hours of last exposure. Progesterone and Estrogen levels in serum were analyzed by Chemiluminescence’s method. Initial serum Progesterone and Estrogen levels in rabbits not exposed to ultrasound were compared with ultrasound exposed serum levels. Results: The estradiol level decreased significantly in group IV (P= 0.014) and progesterone level increased significantly in group III (P=0.011). Conclusion: The current study has revealed that exposure to ultrasound produces changes in hormonal level, if used for longer duration.